Rancang Bangun Prototipe Mesin Potong Berbasis SCADA Menggunakan Mikrokontroler - Tamaji Tamaji; Yoga Alif Kurnia (Universitas Islam Lamongan, 2021)
The automation that is currently developing makes work quickly completed. This automation system is widely used in all fields, especially in industrial environments. In an industrial environment, automation systems are very widely used because they require a fast production process with high yields and high quality, for example, such as the printing industry. The need for a printing machine such as a paper cutting machine is very important. Therefore this research tries to make a SCADA-based cutting machine prototype using a microcontroller so that it can be used or implemented in the printing industry. Tests that have been carried out show that the prototype of this cutting tool is capable of cutting paper to a predetermined size with a measurement error of 6,368%. From this it can be concluded that the cutting tools made in this study are good enough to be used for cutting paper and it is hoped that in the future it can become a tool that makes work easier in the printing industry.